Tanggung Jawab PDAM Tirta Ardhia Rinjani Terhadap Konsumen Yang Dirugikan Dalam Suplai Air Bersih Di Kecamatan Batukliang - Nisa Suriani; H. Djumardin Djumardin; Wahyuddin Wahyuddin (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the form of PDAM Tirta Ardhia Rinjani's responsibility to consumers who are disadvantaged in the supply of clean water in Batukliang District, to find out what efforts are made by the customer when a default occurs by PDAM Tirta Ardhia Rinjani. The type of research used is empirical normative, which examines the application of laws and regulations based on legal concepts and theories to see firsthand the reality on the ground by conducting interviews to obtain field data. The research location is PDAM Tirta Ardhia Rinjani (Central Lombok). Based on the results of the study that: First, the form of PDAM Tirta Ardhia Rinjani's responsibility to consumers who are harmed by direct review of complaints experienced by customers but there is no further action to resolve these complaints and without providing information or explanations given to customers who suffer a loss. Second, the settlement of disputes carried out by the PDAM with customers by seeking and prioritizing the deliberation route or through non-litigation, even if the efforts made cannot be carried out, then proceed to court.